Consumer Response to Live Streaming Shopping using the Stimulus, Organism and Response (SOR) Method Approach - Rahmadini, Desty Devina; Masnita, Yolanda (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to examine and analyze consumer responses to live streaming shopping using the Stimulus, Organism, and Response (SOR) method approach. The indicators of the stimulus include financial bonds and social bonds. The indicator for the organism is trust. Meanwhile, the indicators for the response are customer engagement and purchase intention. The research method used is quantitative. The sample used in this study consists of 194 respondents. The sampling technique employed is purposive sampling. Data is analyzed using the Structural Equation Model (SEM) method. The results of this study indicate that financial bonds have a positive effect on trust. Social bonds have a positive effect on trust. Trust has a positive effect on customer engagement and on purchase intention. Furthermore, Electronic Word of Mouth (E-WOM) positively moderates the effect between trust and purchase intention. Additionally, customer engagement also has a positive effect on purchase intention.